1998
DOI: 10.1021/jp982338+
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Kinetics of the Physisorption of Hydrocarbons on Au(111)

Abstract: Helium atom reflectivity has been used to study the adsorption of a series of n-alkanes, 1-alkenes, and cyclic hydrocarbons on a Au(111) surface. Using this technique, both adsorption and desorption could be observed with high sensitivity under UHV conditions to determine adsorption energies and initial sticking coefficients. For the long-chain n-alkanes studied (C6H14−C12H26), the physisorption energy increases linearly with the chain length by 6.2 ± 0.2 kJ/mol per additional methylene unit. The physisorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
198
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(225 citation statements)
references
References 33 publications
23
198
1
Order By: Relevance
“…24 The desorption of n-alkanes (Nϭ6 to 12͒ from the Au͑111͒ surface was studied by Wetterer et al using helium atom reflectivity. 25 Their conclusions from this study indicate that ⌬E des ‡ (N) increased incrementally by 6.2Ϯ0.2 kJ/mole per methylene unit. In these cases the range of alkyl chain lengths has been limited to Nр12.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…24 The desorption of n-alkanes (Nϭ6 to 12͒ from the Au͑111͒ surface was studied by Wetterer et al using helium atom reflectivity. 25 Their conclusions from this study indicate that ⌬E des ‡ (N) increased incrementally by 6.2Ϯ0.2 kJ/mole per methylene unit. In these cases the range of alkyl chain lengths has been limited to Nр12.…”
Section: Introductionmentioning
confidence: 69%
“…It is important to realize that physically this parameter may include both interaction with the graphite surface and the interactions between adsorbed chains. Previous measurements of the interaction of much shorter alcohols and alkanes with metals such as Ag; 24 Cu, 42,43 and Au 25 have yielded values in the range 5 -6 kJ/mole/CH 2 group. A recent study by Bishop et al has reported segment-surface interaction energies of ϳ8 kJ/mole/CH 2 group for n-alkanes (Nϭ6 to 10͒ adsorbed on Pt͑111͒.…”
Section: Oligomer Desorption Kineticsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] The desorption energy was proportional to numbers of the methylene, ca. 6.5 kJ/mol per methylene unit.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between alkanes and metals has attracted wide attention [1][2][3][4][5]. This is due to the fact that many catalytic processes involve the conversion of saturated hydrocarbons to various products, and also because n-alkane is the simplest molecule among the saturated hydrocarbons.…”
Section: : Introductionmentioning
confidence: 99%
“…This is due to the fact that many catalytic processes involve the conversion of saturated hydrocarbons to various products, and also because n-alkane is the simplest molecule among the saturated hydrocarbons. The adsorption energies of n-alkane molecules on metal substrates are rather small (of the order of 10 kJ/mol/CH 2 chain) [2], and the n-alkane-metal interaction has been categorized to be typical of physical adsorption. However, a softening of the C-H vibration has been observed for the n-alkane/metal system with vibrational spectroscopy [3,4].…”
Section: : Introductionmentioning
confidence: 99%